Praktik Perkawinan Bawah Tangan di DKI Jakarta - Mesraini, Mesraini (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2017)
Abstract: This research study revealed the practice of unregistered marriage in DKI Jakarta focusing on four aspects: forms, causal factors, impacts, and impressions of the doers of the unregistered marriage. Snowball and purposive sampling techniques of field research was employed, involving 18 (eighteen) respondents. In terms of form, there were at least four forms, namely: approved by the legal guardian and marriage vows met the terms and conditions; conducted without the acknowledgement from the legal guardian and thus appointed a marriage guardian; conducted without the acknowledgement from the legal guardian and also the absence of a guardian; and contract marriage. In terms of causal factor, unregistered marriage occured due to several factors: the prospective husband is still a legal husband of another person; without parent approval; avoidance of public ridicule; unwed pregnancy; religious differences; retain retirement rights; and contract marriage. Meanwhile, in terms of impact, the doers of unregistered marriage experienced different impacts. In terms of impression, this research study revealed that the doers turned out to have regretted this marriage, while some others were fine.Abstrak: Tulisan ini mengungkap praktik perkawinan bawah tangan di DKI Jakarta dengan difokuskan pada bentuk, faktor penyebab, dampak, dan kesan pelaku atas perkawinan bawah tangan. Penelitian ini adalah penelitian lapangan dengan menggunakan metode teknik sampling snowball dan purposive. Terdapat 18 (delapan belas) responden dari sejumlah wilayah di DKI Jakarta yang menghasilkan sejumlah temuan. Pada aspek bentuk, setidaknya ada empat praktik perkawinan bawah tangan, yakni: direstui oleh wali nasab serta akad nikahnya memenuhi syarat dan rukun nikah; dilangsungkan tanpa sepengetahuan wali nasab sehingga mengangkat wali nikah; tanpa sepengetahuan wali nasab serta tidak ada wali; dan kawin kontrak. Perkawinan bawah tangan terjadi disebabkan oleh beberapa faktor: calon suami masih berstatus sebagai suami sah dari perkawinan orang lain; tidak memperoleh izin dari orang tua; menghindari cemoohan masyarakat; hamil di luar nikah; perbedaan agama; agar tetap mendapat hak pensiun; dan nikah kontrak. Para pelaku mengalami dampak yang berbeda. Kesan pelaku ternyata ada yang menyesali dan ada yang biasa saja.